Austerity stabilised through European funds: the impact on Slovenian welfare administration and provision. Issue 1 (January 2017) - Samaluk, Barbara
Abstract: The article explores how austerity stabilised through European funds affects institutional change, work organisation and employment relations within Slovenian welfare administration and provision. It shows that increasing dependence upon European funds turns the state into an intermediary characterised by project modes of work organisation that weaken human resource and financial capacities for domestic policy development and provision. It uncovers that project modes of organising, traditionally present within non‐governmental sector, are also entering the public sector. This shift increases the vulnerability of third and public sector workforce and frustrates young and excluded workers' transition into permanent jobs.